2010
DOI: 10.5539/elt.v3n3p211
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-assessment in Promoting Iranian EFL Learners’ Motivation

Abstract: During the last decade, increasing attention has been paid to the role of learner in the process of language learning and testing. Moreover, there is a general consensus in the literature that motivation is one of the key learner characteristics. The objective of this study was to explore the role of journal writing as a self-assessment technique in promoting Iranian EFL learners' motivation. The participants were 60 intermediate students in two groups. The particular self-assessment technique used in the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Data analyses revealed that students were more interested in receiving feedback through screencasting; a finding that was in line with other researchers (Birjandi & Tamjid, 2010;Olesova, 2011;Edwards et al, 2012;Henderson & Philips, 2015).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Data analyses revealed that students were more interested in receiving feedback through screencasting; a finding that was in line with other researchers (Birjandi & Tamjid, 2010;Olesova, 2011;Edwards et al, 2012;Henderson & Philips, 2015).…”
Section: Discussionsupporting
confidence: 73%
“…Few research explored screencasting effect as a feedback tool on writing in asynchronous or blended context (Kerr & Mclaughlin, 2008;Liou & Peng, 2009;Silva, 2012;Thompson & Lee, 2012). Moreover, recent research focused on students' feelings towards different feedback methods on written assignments and how this affects their performance (Birjandi & Tamjid, 2010). Studies reported positive attitudes towards visual and auditory assessment and findings showed that students perceived e-feedback as more valid and valuable than written feedback (Denton, Madden, Roberts, & Rowe, 2008;Crews & Wilkinson, 2010).…”
Section: Related Studiesmentioning
confidence: 99%
“…Some empirical evidence is emerging on the motivational impact of more learner-centred forms of assessment. The introduction of selfassessment has been shown to boost learner motivation in Japanese university settings through a structured project (Kato 2009) and with intermediate Iranian EFL learners through written journals (Birjandi & Tamjid 2010). Lam (2014) presents testimony and a theoretical model of how portfolio assessment of L2 writing can promote student motivation and self-regulated learning.…”
Section: Alternative Forms Of Assessmentmentioning
confidence: 99%
“…To date, however, research has focused primarily on L2 motivation in general (Boo, Dörnyei, & Ryan, ), whereas L2 writing motivation research is still very much in its infancy. Of the limited research on L2 writing motivation, much of it has focused on different ways to enhance student motivation—for example, with the help of computers, gmail docs and blogs, journal writing as a self‐assessment technique to promote motivation, and writing programs that adopt interesting and relevant writing topics (e.g., Birjandi & Hadidi Tamjid, ; Lo & Hyland, ). Other studies have underlined the importance of motivation in student learning of writing.…”
mentioning
confidence: 99%